واقع العرض والطلب السياحي في كل من الج ا زئر وتونس –د ا رسة مقارنة- - حوحو , فطوم (Finance and Business Economies Review, 2023)
Tourism is an important economic sectors in countries with touts its components such as transport, tourism services, hotels and others. So tourism is still received widespread attention from many responsible and overseeing the economic and social development processes ...; Because of its ability to the positive stimulus to other sectors to achieve the targeted development purposes We are trying in this paper diagnose the tourism sector in Algeria and Tunisia through exposure to the most important components of the tourist offer and tourism demand in both countries through a number of tourists and tourism revenue. We determined that the tourism sector in Algeria faces significant constraints, including lack of investment in infrastructure and basic services, and the tourism sector needs to develop a long-term view to be part of the process of economic development when compared to Tunisia.